"PLAYING WITH THE MASK": STUDI PHOTOVOICE ONLINE PERSONA GENERASI Z - Tansri Adzlan Syah; Sovi Septania (Psyche: Jurnal Psikologi, 2024)
ABSTRAKGenerasi Z sebagai generasi digital menjadikan media sosial sebagai ruang untuk terus mendapatkan pengakuan, melalui jumlah followers, like, share dan comment. Apa yang ditampilkan melalui media sosial menjadi sangat penting bagi mereka. Hal ini disebabkan karena generasi Z tidak memiliki pengalaman persimpangan antara dunia analog dan digital (Podara et al., 2021). Menciptakan online persona yang mengagumkan di media sosial adalah sesuatu yang wajar karena karakter mereka sebagai generasi figital menjadikan ruang maya menjadi suatu realitas (Stillman & Stillman, 2019). Online persona dibentuk tanpa menghadirkan impresi yang secara nyata kita miliki, seperti senyuman asli, bahasa tubuh hingga petunjuk non-verbal lain yang menyebabkan identitas diri yang tidak otentik bahkan manipulatif. Tujuan penelitian ini adalah untuk mengeksplorasi bagaimana pengalaman pembentukan online persona pada generasi Z dengan menggunakan pendekatan photovoice. Partisipan penelitian adalah generasi Z yang memiliki rentang usia 18-27 tahun, memiliki jumlah pengikut media sosial diatas 1.000 orang serta aktif menampilkan diri di media sosial. Partisipan mengikuti pelatihan smart photography kemudian secara mandiri mengambil foto selama 7 hari dengan smartphone lalu di unggah di media sosial masing-masing. Penggalian pengalaman dan permaknaan foto oleh partisipan menggunakan wawancara mendalam yang kemudian dianalisis secara tematik. Hasil analisis tematik dengan menggunakan program Nvivo 12 menunjukan pengalaman pembentukan online persona sebagai strategi presentasi diri yang melibatkan pemilihan foto sebagai cues (isyarat/sinyal), kekuatan captions (keterangan gambar), keterampilan sunting foto dan ketepatan pemilihan waktu unggah di media sosial. Selain itu, pembentukan online persona terkait dengan tiga tujuan yaitu untuk disukai (ingratiation), promosi diri (self-promotion) dan agar menjadi inspirasi/contoh (exemplification). ABSTRACTGeneration Z, being a digital cohort, utilizes social media platforms as a way to consistently acquire acknowledgment by increasing the quantity of followers, likes, shares, and comments. The content exhibited on social media platforms assumes significant importance for individuals. This is due to the fact that Generation Z lacks exposure to the convergence of the physical and digital realms [1]. Developing exceptional online personas on social media is an inherent phenomenon, since their persona as a fictional generation materializes in the virtual realm. The formation of an online persona occurs without the deliberate presentation of true impressions, such as a genuine smile, body language, and other non-verbal clues. This process results in the creation of an authentic self-identity that is free from manipulation. The objective of this study is to investigate the process of online persona construction among individuals belonging to Generation Z through the utilization of photovoice methodologies. The research participants consisted of individuals from generation Z, specifically between the ages of 18 and 27, possessed a social media followed by over 1,000 followers and actively engaged in self-presentation on social media platforms. Participants engage in a comprehensive training program on smart photography techniques. Subsequently, they are required to capture photographs using a smartphone camera for a duration of 7 days and subsequently share them on their own social media platforms. The process of data extraction will involve conducting in-depth interviews to gather a comprehensive understanding of their online persona’s building experience. This information will then be examined thematically, taking into account the participants' descriptions of the images they captured. The results of the thematic analysis conducted using the Nvivo 12 software revealed that the online persona is associated with a self-presentation strategy that encompasses the deliberate selection of photo displays as cues, the effectiveness of captions, proficiency in capturing displays (photos or videos), and the precision in choosing upload times. The self-presentation strategy is implemented with three primary goals: to cultivate favor and approval (ingratiation), to promote oneself, and to serve as a source of inspiration or example (exemplification).